Detection of pepsin in sputum: a rapid and objective measure of airways reflux. Issue 1 (5th November 2015) - Strugala, Vicki; Woodcock, Andrew D.; Dettmar, Peter W.; Faruqi, Shoaib; Morice, Alyn H.
The diagnostic test, Peptest (RD Biomed Ltd, Cottingham, UK), detects pepsin in expectorated saliva and is established as a simple, noninvasive measure of reflux of gastric contents. It has been used to detect pepsin A in patients with both gastro-oesophageal reflux disease (GORD) and extra-oesophageal reflux into the laryngopharynx and airways [1–5]. Detection of salivary pepsin (Peptest) may be a useful adjunct in the diagnosis of airway reflux http://ow.ly/T7B0l